Management of accidental hypothermia: an established extracorporeal membrane oxygenation centre experience. (April 2019) - Balik, Martin; Porizka, Michal; Matousek, Vojtech; Brestovansky, Petr; Svobodova, Eva; Flaksa, Marek; Rulisek, Jan; Mlejnsky, Frantisek; Hodkova, Gabriela; Grus, Tomas; Vobruba, Vaclav; Belohlavek, Jan
Introduction: Data on management of severe accidental hypothermia published from an established high-volume extracorporeal membrane oxygenation centre are scarce. Methods: A total of 28 patients with intravesical temperature lower than 28°C on admission were either treated with veno-arterial extracorporeal membrane oxygenation or rewarmed conservatively. Results: A total of 10 patients rewarmed on veno-arterial extracorporeal membrane oxygenation (age: 37 ± 12.6 years) and 18 conservatively (age: 55.2 ± 11.2 years) were collected over a course of 5 years. The dominant cause was alcohol intoxication with exposure to cold (39%), 12 patients were resuscitated prior to admission. The admission temperature in the extracorporeal membrane oxygenation group (23.8 ± 2.6°C) was lower than in the non–extracorporeal membrane oxygenation group (26.0 ± 1.5°C, p = 0.01). The peripheral percutaneous veno-arterial extracorporeal membrane oxygenation was always cannulated in malignant arrhythmias causing refractory cardiac arrest. The typical extracorporeal membrane oxygenation blood flow was 3-4 L/minute and sweep gas flow 2 L/minute, the median extracorporeal membrane oxygenation duration was 48.3 (28.1-86.7) hours. The median rates of rewarming did not differ (0.41 (0.35-0.7)°C/hour in extracorporeal membrane oxygenation and 0.77 (0.54-0.98)°C/hour in non–extracorporeal membrane oxygenation, p = 0.46) as well as the admission arterial lactate, pH and potassium. Their development was not different between the groups except for higher pH between the third and ninth hour of rewarming in the extracorporeal membrane oxygenation group. The hospital mortality was 10% in the extracorporeal membrane oxygenation group and 11.1% in the non–extracorporeal membrane oxygenation group with the median last Glasgow Coma Scale 15 and Cerebral Performance Score 1. Conclusion: Veno-arterial extracorporeal membrane oxygenation for severe hypothermia shows promising outcome data collected in an extracorporeal membrane oxygenation/extracorporeal cardiopulmonary resuscitation centre located in a European urban area. Except for presence of refractory cardiac arrest, the established hypothermia-related prognostic indicators did not differ between patients in need for extracorporeal membrane oxygenation and those rewarmed without extracorporeal membrane oxygenation.